Spinoza's political philosophy the factory of imperium - Caporali, Riccardo (Spinoza studies., 2022)
Riccardo Caporali examines of all of Spinoza's works while addressing the challenges imposed by the historical circumstances at the time. Focusing on Spinoza's constant preoccupation with the relationship between metaphysics and politics, Caporali shows that it takes different forms in his various major works.